Very low doses of heavy oxygen ion radiation induce premature ovarian failure. Issue 2 (August 2017) - Mishra, Birendra; Ripperdan, Ryan; Ortiz, Laura; Luderer, Ulrike
Abstract : Astronauts are exposed to charged particles during space travel, and charged particles are also used for cancer radiotherapy. Premature ovarian failure is a well-known side effect of conventional, low linear energy transfer (LET) cancer radiotherapy, but little is known about the effects of high LET charged particles on the ovary. We hypothesized that lower LET (16.5 keV/µm) oxygen particles would be less damaging to the ovary than we previously found for iron (LET = 179 keV/µm). Adult female mice were irradiated with 0, 5, 30 or 50 cGy oxygen ions or 50 cGy oxygen plus dietary supplementation with the antioxidant alpha lipoic acid (ALA). Six-hour after irradiation, percentages of ovarian follicles immunopositive for γH2AX, a marker of DNA double strand breaks, 4-HNE, a marker of oxidative lipid damage and BBC3 (PUMA), a proapoptotic BCL-2 family protein, were dose dependently increased in irradiated mice compared to controls. One week after irradiation, numbers of primordial, primary and secondary follicles per ovary were dose dependently decreased, with complete absence of follicles in the 50 cGy groups. The ED50 for primordial follicle destruction was 4.6 cGy for oxygen compared to 27.5 cGy for iron in our previous study. Serum FSH and LH concentrations were significantly elevated in 50 cGy groups at 8 week. Supplementation with ALA mitigated the early effects, but not the ultimate depletion of ovarian follicles. In conclusion, oxygen charged particles are even more potent inducers of ovarian follicle depletion than charged iron particles, raising concern for premature ovarian failure in astronauts exposed to both particles during space travel.